Misinformation technology: Internet use and political misperceptions in Africa - (:unkn) unknown (My University, 2024)
The use of the Internet to access news has an impact on African citizens' perceptions of democracy. Using repeated cross-sectional data from the Afrobarometer survey across 35 African countries over the period 2011-2018, along with an instrumental variable approach, allows addressing potential endogeneity bias between Internet use and citizens' perceptions. The results indicate that using the Internet to obtain information has a significant negative effect on both the preference for and the perception of the extent of democracy. This negative effect is due to several factors. First, Internet use erodes trust in government institutions, mainly in the parliament and the ruling party. It increases the perception that parliament members are involved in corruption. In addition, the erosion of trust is correlated with more political mobilization, in the form of greater participation in demonstrations and voting. These results echo the existing literature and, in particular, hint at the risks of reversal of nascent democratization processes. Finally, the Internet seems to act as a misinformation channel. On the one hand, Internet users' perception of the extent of democracy and perception of the corruption of legislators diverge from experts' assessments. On the other hand, Internet use increases the likelihood of inconsistency in respondents' stances on their preference for democracy. The Internet is not a neutral information channel: it tends to undermine citizens' preference for democracy while also altering perceptions about political institutions.
Keywords: African Research